Adeno-associated virus vector intraperitoneal injection induces colonic mucosa and submucosa transduction and alters the diversity and composition of the faecal microbiota in rats - Ma, Li-Tian; Lian, Jing-Xuan; Bai, Yang; Shang, Meng-Juan; Zhang, Zhe-Zhe; Wu, Fei-Fei; Chen, Jing; Meng, Xian-Bo; Zheng, Jin; Li, Tian; Li, Yun-Qing; Wang, Jing-Jie (Frontiers in Cellular and Infection Microbiology, 2022)
Background Viral vector technology, especially recombinant adeno-associated virus vector (rAAV) technology, has shown great promise in preclinical research for clinical applications. Several studies have confirmed that rAAV can successfully transduce the enteric nervous system (ENS), and rAAV gene therapy has been approved by the Food and Drug Administration (FDA) for the treatment of the early childhood blindness disease Leber congenital amaurosis and spinal muscular atrophy (SMA). However, until now, it has not been possible to determine the effect of AAV9 on intestinal microbiota. Methods We examined the efficiency of AAV9-mediated ascending colon, transverse colon and descending colon transduction through intraperitoneal (IP) injection, performed 16S rRNA gene amplicon sequencing and analysed specific faecal microbial signatures following AAV9 IP injection via bioinformatics methods in Sprague–Dawley (SD) rats. Results Our results showed (1) efficient transduction of the mucosa and submucosa of the ascending, transverse, and descending colon following AAV9 IP injection; (2) a decreased alpha diversity and an altered overall microbial composition following AAV9 IP injection; (3) significant enrichments in a total of 5 phyla, 10 classes, 13 orders, 15 families, 29 genera, and 230 OTUs following AAV9 IP injection; and (4) AAV9 can significantly upregulate the relative abundance of anaerobic microbiota which is one of the seven high-level phenotypes that BugBase could predict. Conclusion In summary, these data show that IP injection of AAV9 can successfully induce the transduction of the colonic mucosa and submucosa and alter the diversity and composition of the faecal microbiota in rats.